Kerjasama Jaringan Perpustakaan di Indonesia: - Annisya Annisya; Rifqa Amalia Zuhri; Restiana, Restiana,; Yusniah Yusniah (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Collaborative Partnerships are critical to driving demand and meeting Demand readers. The availability of collaboration and networking services in the system library for all individuals is critical to the success of the push. This increases service user and technical capacity, enhances resource sharing, reduces duplication, and provides efficient services. When creating the basis for collaboration and networking in libraries in general, several factors must be considered. Keywords: National Library, Collaboration, Library Network, National Library Collaboration, Collaboration Network